A NOTCH3 pathogenic variant influences osteogenesis and can be targeted by antisense oligonucleotides in induced pluripotent stem cells - Ernesto Canalis; Jungeun Yu; Lauren Schilling; Paymaan Jafar-nejad; Michele Carrer (PLoS ONE, 2025)
Lateral Meningocele Syndrome (LMS), a disorder associated with NOTCH3 pathogenic variants, presents with neurological, craniofacial and skeletal abnormalities. Mouse models of the disease exhibit osteopenia that is ameliorated by the administration of Notch3 antisense oligonucleotides (ASO) targeting either Notch3 or the Notch3 mutation. To determine the consequences of LMS pathogenic variants in human cells and whether they can be targeted by ASOs, induced pluripotent NCRM1 and NCRM5 stem (iPS) cells harboring a NOTCH36692-93insC insertion were created. Parental iPSCs, NOTCH36692-93insC and isogenic controls, free of chromosomal aberrations as determined by human CytoSNP850 array, were cultured under conditions of neural crest, mesenchymal and osteogenic cell differentiation. The expected cell phenotype was confirmed by surface markers and a decline in OCT3/4 and NANOG mRNA. NOTCH36692-93insC cells displayed enhanced expression of Notch target genes HES1, HEY1, 2 and L demonstrating a NOTCH3 gain-of-function. There was enhanced osteogenesis in NOTCH36692-93insC cells as evidenced by increased mineralized nodule formation and ALPL, BGLAP and BSP expression. ASOs targeting NOTCH3 decreased both NOTCH3 wild type and NOTCH36692-93insC mutant mRNA by 40% in mesenchymal and 90% in osteogenic cells. ASOs targeting the NOTCH3 insertion decreased NOTCH36692-93insC by 70–80% in mesenchymal cells and by 45–55% in osteogenic cells and NOTCH3 mRNA by 15–30% and 20–40%, respectively. In conclusion, a NOTCH3 pathogenic variant causes a modest increase in osteoblastogenesis in human iPS cells in vitro and NOTCH3 and NOTCH3 mutant specific ASOs downregulate NOTCH3 transcripts associated with LMS.